Tourist Attraction Development after Revitalization of Taman Mini Indonesia Indah - Rainanto, Bambang Hengky; Wiranti, Putri; Pujiastuti, Sri; Suryanti, Cecilia Valentina Srihadi; Bon, Abdul Talib; Melle, Jonathan van; Rudyanto, Bambang (Stupa, 2024)
This study investigates the development of tourist attractions at Taman Mini Indonesia Indah (TMII) following its revitalization, using the 4A framework: Attractions, Accessibility, Amenities, and Ancillary Services. A qualitative descriptive approach was applied, with data analyzed using Nvivo 12 Plus to facilitate thematic coding and identify patterns from interviews and observations. The findings highlight substantial improvements across all 4A components. TMII’s attractions, including regional pavilions, museums, and thematic parks, have diversified and enhanced, appealing to a broader range of visitors. Accessibility has been significantly improved through upgraded transportation infrastructure, such as roads and public transit options. Enhanced amenities, including parking facilities, restrooms, and dining areas, have increased visitor convenience and satisfaction. Ancillary services, such as information centers and interactive educational activities, further enrich the tourism experience. Additionally, three key post-revitalization dimensions are identified: physical, economic, and social. The physical dimension involves the development of attractions, infrastructure upgrades, and environmental conservation efforts. Economically, TMII has expanded income sources, empowered small and medium enterprises, invested in infrastructure, and hosted events, strengthening its position as a premier destination. Socially, TMII serves as a center for education, cultural engagement, and community interaction, fostering a dynamic and inclusive social environment.